Dying the right-way? Interest in and perceived persuasiveness of parochial extremist propaganda increases after mortality salience - Frischlich, Lena; Rieger, Diana; Hein, Maia; Bente, Gary (Frontiers in Psychology, 2015)
Research on parochial altruism demonstrated that hostility toward out-groups (parochialism) represents the dark side of the willingness to benefit one’s in-group even at own costs (altruism). Parochial aggression thereby emerged mainly under conditions of threat. Extremist propaganda videos, for instance by right-wing extremists, try to capitalize on parochial altruistic mechanism by telling recipients sharing their national identity that this nation is under threat wherefore they for have to join the extremist’s cause to prevent the extinction of their nation. Most of the time, propaganda videos are rated as uninteresting and non-persuasive by the target audience. Yet, evolutionary media psychology posits that the interest in and effectiveness of media increases when evolutionarily relevant problems are addressed. Consequently, interest in parochial altruistic right-wing extremist messages should increase under conditions of threat. The current study tested this assumption by randomly assigning German non-Muslims (N = 109) to either an existential threat (here: mortality salience) or a control condition and asking them to evaluate extremist propaganda that addressed them as either in-group members (right-wing extremists) or as out-group members (Islamic extremists). In support of the hypotheses, subjects under conditions of threat reported a higher interest in the right-wing extremist propaganda and perceived it as more persuasive. We discuss the results concerning the implications for evolutionary media psychology and the transmission of parochial altruism in propaganda videos.